Comparative analysis of the microbial composition of three packaged sliced dry-cured hams from a Chinese market - Luo, Xin; Shen, Ying (Frontiers in Microbiology, 2025)
Ham, a widely consumed and culturally significant food, undergoes fermentation and aging processes that contribute to its distinctive flavor and texture. These processes are influenced by a complex interplay of microbial communities, which vary by the production region. Understanding these microbial dynamics can provide insights into flavor development and quality improvements in ham. In this study, the microbial communities found in ham produced in three distinct regions were compared, revealing that bacteria have a more dominant role in shaping the overall microbiota than fungi. Notably, each type of ham exhibited a unique microbial profile, although those from similar regions shared more similar profiles. Specific bacterial biomarkers were identified for each regional ham: Lactobacillus and Tetragonococcus in Serrano prosciutto, Odoribacter, Alistipes, Staphylococcus, and Akkermansia in Jinhua prosciutto, and Pseudomonas, Blautia, and Bacteroides in Xuanwei prosciutto. The microbial network analysis identified closer associations between microorganisms in the domestically produced Chinese hams than in the Spanish ham, suggesting limited foreign microbial invasions that contributed to a richer, more stable flavor. These findings offer new insights into how microbial interactions shape the development of flavor and quality in ham and clarify future strategies for improving the production process by leveraging microbial communities.